La professionnalité enseignante dans le débat en classe : une étude de cas en EMC pour faire émerger le milieu de vie de l'élève - Jean-Luc Denny; Eric Flavier
The article documents a practice of classroom debate centred on the student's living environment aimed at tackling all forms of inequalities. It describes the impact of its implementation upon teachers' professionality by highlighting the comprehensive and transformative dimension induced by the ergological approach (Schwartz, 2000).A longitudinal data collection system (audiovisual recordings of the debates and self-confrontation interviews with three teachers) was set up over a school year. The results show professional development based on a triple process leading from the instrumentalization of students' experiences to a sense of inefficiency, from a change of reference frame to a destabilization of the professional genre and from the experience of letting go to that of the professional standards giving in.Our research ends of the design of a training system that aims to analyze the work of the activity as a formative process in schools.